SARS-CoV-2 Infection During Induction Chemotherapy in a Child With High-risk T-Cell Acute Lymphoblastic Leukemia. Issue 6 (August 2021) - Dantonello, Tobias M.; Kartal-Kaess, Mutlu; Aebi, Christoph; Suter-Riniker, Franziska; Busch, Jasmin D.; Kubetzko, Susanne; Bourquin, Jean-Pierre; Roessler, Jochen
Abstract : The clinical course of SARS-CoV-2 infection (COVID-19) in children with hematologic malignancies is unclear. We describe the diagnosis, treatment and outcome of a 4-year-old boy with high-risk acute lymphoblastic leukemia and COVID-19. Regardless of immunosuppressive induction chemotherapy his symptoms remained moderate. He received only supportive treatment. Seroconversion occurred in a similar period as in immunocompetent adults. Despite prolonged myelosuppression he did neither acquire secondary infections nor did the treatment delay caused by the infection have a measurable negative impact on the residual disease of acute lymphoblastic leukemia. Intriguingly, residual leukemia even decreased even though he did not receive any antileukemic therapy.